BERMAIN SAINS SEBAGAI METODE YANG EFEKTIF DALAM PEMBELAJARAN SAINS UNTUK ANAK USIA DINI - Dewi Setiawati Gusti Ayu; Ekayanti Ni Wayan (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Early childhood is a period of fundamental human development or known as the golden period because at this time the physical, intellectual, motoric, emotional, social and language development of children is taking place rapidly. Science must be introduced as a provision of knowledge for early childhood who continues to grow and develop. The introduction of science in early childhood is an effort to foster critical character, curiosity, thoroughness, exploration to find answers and think regularly through fun activities. Science is introduced from an early age as well as preparation for learning at a higher level. This research is a literature study which aims to examine the activities of playing science as an effective method of learning science for early childhood. The types of activities in playing science are: 1) playing with physical science, 2) playing with the living things science and 3) playing on earth and environmental science. Based on the results of a literature review, it was found that the playing science method was effective in early age science learning, including; improve science skills and science learning outcomes, introduce and improve basic science process skills and improve children's science concepts.